PENGARUH PENILAIAN KINERJA DAN ETOS KERJA TERHADAP PROMOSI JABATAN PADA KANTOR ADMINISTRASI VETERAN DAN CADANGAN I/12 LANGKAT KODAM I/BUKIT BARISAN - Jenny Jenny; awaludin awaludin (Fakultas Ekonomi Universitas Tjut Nyak Dhien Medan, 2022)
This study aims to determine the effect of performance appraisal on the promotion of personnel of Kaminvetcad I/12 Langkat Kodam I/Bukit Barisan, to determine the effect of work ethic on the promotion of positions of personnel of Kaminvetcad I/12 Langkat Kodam I/Bukit Barisan, and to determine the effect of performance appraisal and work ethic. towards the Promotion of the Position of the Vetcad I/12 Military Command Personnel I/12 Langkat Kodam I/Bukit Barisan. This research is a descriptive quantitative questionnaire instrument, the research population is 45 people, the sample population uses a saturated sample so that the research sample is 45 people. The results obtained that the coefficient value of the tcount variable Performance appraisal is 5,150 and the ttable value is 2,015, the tcount > ttable (5,150 > 2,015) and the sig value < 0.05 (0.000 < 0.05), the coefficient value for the variable tcount is 2.723 and the ttable value is 2.015 then the value of tcount > ttable (2.723 > 2.015) and the value of sig <0.05 (0.009 <0.05). Furthermore, the F value of the variable Performance appraisal and work ethic is 20,729 and the value of Ftable is 2,816, so Fcount > Ftable (20,729 > 2.816 and the value of sig < 0.05 (0.000 < 0.05) The RSquare value is 0.727 or R2 x 100% of 72.70% , meaning that the research variable makes a major contribution in explaining the promotion of personnel positions by 72.70% while the remaining 27.30% The influence of other factors Performance appraisal has a significant effect on the promotion of personnel of Kaminvetcad I/12 Langkat Kodam I/Bukit Barisan, Work ethic has a significant effect to the promotion of personnel positions of Kaminvetcad I/12 Langkat Kodam I/Bukit Barisan and simultaneously Performance Assessment and work ethic have a significant effect on the Promotion of positions of personnel of Kaminvetcad I/12 Langkat Kodam I/Bukit Barisan.